Clinical Characteristic Analysis of Seven Children With Bickerstaff Brainstem Encephalitis in China - Ding, Yifeng; Yu, Lifei; Zhou, Shuizhen; Zhang, Linmei (Frontiers in Neurology, 2020)
Objective: To summarize the clinical, electrophysiological, neuroimaging, and immunological characteristics of seven cases of Bickerstaff brainstem encephalitis (BBE) in China and to determine whether certain clinical features suggestive of BBE can facilitate diagnosis and treatment. Patients and Methods: The clinical data of seven BBE patients treated at the Children’s Hospital of Fudan University between 2016 and 2019 were retrospectively analyzed. The clinical and laboratory characteristics of the BBE patients were studied. Results: The seven patients in this study included four females and three males, and the median age at diagnosis was 5.3 years (interquartile range: 3.0-7.1 years). All seven patients had an acute onset with a preinfection history. Seven cases of acute extraocular paralysis, ataxia, and an impaired level of consciousness, two cases of tendon hyperreflexia, one case of positive pathology, and five cases of cranial nerve involvement (the facial nerve and oculomotor nerve) were noted. Cerebrospinal fluid (CSF) examination of five patients showed albuminocytologic dissociation. Electromyography (EMG) was used to examine seven patients; the results were normal in four patients, showed axonal involvement in two patients, and showed demyelination in one patient. The head magnetic resonance imaging (MRI) results of all seven patients were normal. Electroencephalogram (EEG) background activity in the five monitored patients was slowed down. Seven patients underwent serum antibody testing, three of whom were positive for anti-GQ1b antibody, while one was positive for anti-GM1 antibody. Three patients received glucocorticoid combined with intravenous immunoglobulin (IVIG) therapy, and four received only IVIG therapy. One patient required a nasal catheter for oxygen during the disease course, and left upper limb muscle dysfunction (grade III muscle strength of the left upper limb) was observed during the six-month follow-up. The other six patients had a good prognosis and no dysfunction. Conclusion: Our study identified clinical, imaging, and treatment characteristics that may have prognostic value for pediatric BBE. The positive rate of head MRI was low, the positive rate of serum anti-GQ1b ganglioside antibody was low, and the therapeutic effect of IVIG therapy was good.